Leiko Ikemura : Ozean. Ein Projekt - Malsch, Friedemann; Bronfen, Elisabeth; Malsch, Friedemann; Pühringer, Alexander; Kunstmuseum Liechtenstein, Vaduz (Ostfildern-Ruit : Hatje Cantz Verlag Ostfildern-Ruit, 2002)
The Japanese-born artist Leiko Ikemura has been living in Europe for almost thirty years. Her artistic activities are characterized by an exploration of these two cultures, featuring paintings, drawings and sculptures that always deal with questions central to human existence. If Ikemura still concentrated on probing allegorical picture narratives in the eighties, around 1990 her interest shifted to cosmological problems manifesting themselves in transcendence and religious aspects. Since then, her works have predominantly been living from color with very little narrative, depicting atmospherical situations of bodies in space. For this book, the artist created numerous new works, paintings, watercolors and sculptures whose central theme is the depiction of space extending beyond the material and the measurable, a contemplative space of spirituality and sensuality. The various media of expression compliment each other to create a strong spatial effect for the viewer. He or she is drawn into an event which can no longer be assigned to one particular form of culture.
Leiko Ikemura : Ozean. Ein projekt, Kunstmuseum Liechtenstein, Vaduz, from 8 March to 12 May 2002
biog., bibliog., ind. tent. p. 95
Duits
Engels
boek
Keywords: Ikemura, Leiko